A new species of Colpolopha Stål, 1873 (Orthoptera: Romaleidae) from Brazil - Mariño-Pérez, Ricardo; Pocco, Martina E. (Zootaxa, 2023)
Colpolopha minuta sp. nov. (Orthoptera: Romaleidae) is described from Floresta Nacional do Aripe near Crato in Ceará State, Brazil from 17 specimens collected by Moacyr Alvarenga deposited at the Insect Collection of the University of Michigan Museum of Zoology. This new species is characterized by its small size and brachypterous tegmina compared to other known Colpolopha species. A comparison with other short-winged Colpolopha species is provided. A discussion about some iNaturalist records is provided in order to help us identify possible new records or species in the region.